Faculty facilitators' and standardized family members (SFMs) perceptions of student teamwork during an interprofessional education simulation workshop. Issue 6 (2nd November 2018) - Hadley, Diane E.; Packel, Lora; Kim, Hyejin; Darrah, Neha J.; LaMarra, Denise; Bradway, Christine
ABSTRACT: Standardized patients can be trained to portray standardized family members (SFMs) for interprofessional education (IPE) initiatives to maximize student learning. To date, studies of IPE often focus on student learning outcomes rather than on the feedback and perspectives of SFMs and faculty facilitators (FFs), The purpose of our study was to examine SFMs' and FFs' perspectives immediately after participating in an IPE workshop. SFMs and FFs completed a semi-structured questionnaire consisting of open-ended questions to identify positive and challenging aspects of interactions with health professions students during an IPE workshop. A directed content analysis approach was used to assess written feedback (N = 29) from SFMs and FFs. Study findings highlight many similar themes between SFMs and FFs as well as minor differences regarding recognition of emotion and communication transitions. SFMs and FFs both agreed, however, that these are areas for further development by students to improve communication. Our study adds insight into SFMs' and FFs' feedback immediately after an IPE workshop.